Fabrication of Long‐Lasting Superhydrophilic Anti‐Fogging Film Via Rapid and Simple UV Process - Jae Hwan Jung; Yu Bin Kang; Chungryong Choi (Advanced Science)
Abstract Surface fogging is a common phenomenon that can result in restricted visibility, reduced light absorption, and image distortion. Although both hydrophobic and hydrophilic surfaces are effective in preventing this phenomenon, typical coatings in both have limitations, including low durability and the need for frequent reapplication. To address these issues, a highly durable anti‐fogging film that lasts over five weeks, even under high moisture conditions, while maintaining a promising degree of transparency (> 60%) is developed. A novel statistical random copolymer containing superhydrophilic and photo‐crosslinkable segments that can be simultaneously crosslinked and chemically bonded to various substrates via a simple ultraviolet (UV) irradiation process is synthesized. Notably, the chemical bonding between the anti‐fogging coating and substrate improves not only the durability but also the resistance to external forces and environmental changes. Furthermore, this film is versatile and applicable to diverse substrates, such as car windshields, polymer films, and aluminum foil. The innovative strategy offers a simple, rapid process and durable anti‐fogging performance with broad applications in the automotive industry, optical devices, and building materials.